Chromosome-scale genome assembly of three-spotted seahorse (Hippocampus trimaculatus) with a unique karyotype - Ning Li; Xinhui Zhang; Xin Liu; Xueqiang Lin; Cancan Hu; Jieming Chen; Shengchao Wang; Dong Zhang; Shuguang Wei; Qiong Shi (Scientific Data)
Abstract Three-spotted seahorse (Hippocampi trimaculata) is a unique fish with important economic and medicinal values, and its total chromosome number is potentially quite different from other seahorse species. Herein, we constructed a chromosome-level genome assembly for this special seahorse by integration of MGI short-read, PacBio HiFi long-read and Hi-C sequencing techniques. A 416.57-Mb haplotypic genome assembly was obtained. Subsequently, 99.38% of its scaffold sequences were anchored onto 18 chromosomes, with identification of 29.1% repeat sequences in the assembled genome. Additional karyotype analysis validated the diploid chromosomes of 2n = 36, which are remarkably different from other seahorses’ 2n = 42 or 44. The genome completeness (BUSCO score: 96.5%, CEGMA score: 97.87%) confirmed that this chromosome-scale assembly is indeed of high quality. Moreover, a total of 18,712 protein-coding genes were annotated, of which 96.36% could be predicted with functions. Based on construction of a phylogenetic tree, we estimated that Hippocampus and Syngnathoides diverged approximately 50.1 million years ago (Mya). Taken together, our genome data presented in this study provide a valuable genetic resource for numerical chromosome changes and in-depth evolutionary and functional investigations, as well as conservation and molecular breeding of this endangered teleost.